Kurier Mazowsza . pismo ulotkowe Grup Oporu "Solidarni", no. 35, 1989 - Leski, Krzysztof; Klincewicz, Teodor; Grydniewski, Kuba; Jaczyński, Grzegorz (Grupy Oporu "Solidarni", 1989)
Creation and circulation: From issue no. 72(1989) published legally; In 1989 published in two formats 15 and 30 cm. The 30 cm edition with singlesided print was designed for noticeboards.